PEMBERIAN INTERVENSI SENAM LANSIA PADA LANSIA DENGAN NYERI LUTUT - Afifka Dyah Ayu D; Bambang Edi Warsito (Jurusan Keperawatan, Universitas Diponegoro, 2012)
Aging is a process of eliminating the network's ability to repair itself gradually. Elderly tend to get the decreased on the musculoskeletal system. The decreased of the musculoskeletal system is characterized by pain in the joints, for example the knee joint. Knee pain is a regenerative joint diseaseand also one signs and symptoms of osteoarthritis. One way to reduce the knee pain is using the non-pharmacologic therapy with elderly gymnastic. The purpose of this research is to provide elderly exercise intervention in older adults with knee pain to reduce the pain. The benefit of this research is to train the ability of muscles and joints to reduce the knee pain scale in the elderly. The method used a quantitative research design with experimental and one type of group pre-post test design. The population in this study were elderly men and women in the Social Rehabilitation Unit